IMPLEMENTING THE PRINCIPLES OF SOCIAL JUSTICE AND EQUALITY IN EDUCATION: A LITERATURE REVIEW OF EFFORTS TO ELIMINATE DISCRIMINATION AND BUILD MUTUAL RESPECT IN SCHOOLS - Aslan Aslan; Rizka Fadliah Nur (International Journal of Teaching and Learning, 2025)
This study aims to examine the application of the principles of social justice and equality in education through a literature review of efforts to eliminate discrimination and build mutual respect in schools. This study uses a literature study method with a descriptive qualitative approach, analysing various sources such as scientific journals, books, research reports and education policy documents. The results show that although various forms of discrimination - such as economic, gender, racial and against students with special needs - are still found in the school environment, concrete efforts have been made to overcome them. These efforts include teacher training, inclusive curriculum development, the implementation of anti-discrimination policies, and the involvement of parents and communities in building a culture of mutual respect. By consistently applying the principles of social justice and equality, schools can become an inclusive, fair and harmonious environment, and form a generation that is tolerant and respectful of differences.